Compensation strategies to enact new governance frameworks for SDG transformations (Public Sector Economics - submission site, 2019)
There is an emerging consensus at international level that systemic transformations are needed to achieve the Sustainable Development Goals (SDGs). Such transformations require paradigm shifts in policies, with appropriate governance frameworks to implement them. Fundamental transformations are likely to generate winners and losers; the latter may act strategically to deter transformation. Most governance literature points at mutual gains negotiation methods to prevent the emergence of losers and create ‘win-win’ package deals. In this article a different – and less researched – approach will be discussed: (economic) compensation strategies. Drawing on the political economy literature of reform in transition economies, I propose three compensation strategies to buy out or weaken the opposition of strategic losers – big bang, optimal sequencing and divide-and-rule governance reforms – that can help to frame discussions around the political feasibility of new governance frameworks for SDG transformations. The paper suggests that careful consideration needs to be given to the design of these compensation packages, since history tells us that buying acceptance for reform can involve not just variation in economic outcomes, it can also have long-term political implications and distributional effects.